1994
DOI: 10.1002/mrm.1910320206
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular and extracellular spaces and the direct quantification of molar intracellular concentrations of phosphorus metabolites in the isolated rat heart using 31P NMR spectroscopy and phosphonate markers

Abstract: To quantify metabolite and cation concentrations using NMR spectroscopy, the volumes of intracellular and extracellular spaces must be known. We describe a simple 31P NMR spectroscopic method that employs dimethyl methylphosphonate (DMMP) as a marker of total water space and phenylphosphonate (PPA) as a marker of extracellular space to determine intracellular and extracellular space volumes in the isolated, perfused rat heart. In vivo and in vitro radiolabel studies were used to verify this method. The differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 18 publications
6
40
0
2
Order By: Relevance
“…1 and 5). In agreement with other heart studies on phosphorylated compounds (30, 36, 37), a slight cardioprotection was exerted by DEPMPH on reperfused hearts (Table III), whereas this aspect has not been investigated in detail in previous studies on alkylphosphonate NMR probes (21)(22)(23)(24). As a tentative explanation for the cardioprotective effect of DEPMPH on the reperfused heart, it has been hypothesized that pro-oxidant transition metal ions and/or Ca 2ϩ released from the post-ischemic heart may have been inactivated by chelation on the diethoxyphosphoryl group of the pyrrolidine (30).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…1 and 5). In agreement with other heart studies on phosphorylated compounds (30, 36, 37), a slight cardioprotection was exerted by DEPMPH on reperfused hearts (Table III), whereas this aspect has not been investigated in detail in previous studies on alkylphosphonate NMR probes (21)(22)(23)(24). As a tentative explanation for the cardioprotective effect of DEPMPH on the reperfused heart, it has been hypothesized that pro-oxidant transition metal ions and/or Ca 2ϩ released from the post-ischemic heart may have been inactivated by chelation on the diethoxyphosphoryl group of the pyrrolidine (30).…”
Section: Discussionsupporting
confidence: 90%
“…The data from Figs. 1 and 5 show that DEPMPH, even perfused at the lowest concentration (5 mM) among those used in previous NMR studies with charged alkylphosphonates (21)(22)(23)(24), reasonably penetrates heart and liver tissue, distributing into extra-and intracellular compartments to provide a satisfactory NMR detection. In cell studies where aminoalkylphosphonates have been used as 31 P NMR pH probes, it was found that compounds having a low dipole moment (i.e.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…17 Clarke et al combined the advantages of these agents to measure the intra/extracellular water ratio and energy metabolism in the isolated heart. 18 For measurements of the trans-membrane distribution of cations, a series of extracellular shift reagents with variable affinities and characteristics have been used, including dysprosium tripolyphosphate 10,11 11 This estimate assumes that the intracellular environment is not affected by the cationic shift reagent, neglecting the bulk susceptibility effects that may cause an overestimation of the intracellular space. This technique also assumes full visibility of intracellular sodium, or requires correction for the NMR-visibility coefficient.…”
Section: Nmr Measurements Of the Intracellular Water Spacementioning
confidence: 99%
“…In variance, the myocytes swell in conditions of sustained no-flow ischemia. 18,40,42,43 Swelling is partially due to import of sodium through sodium channels, cotransport (Na/K/2Cl) and antiport (Na/H) systems, and not due to inhibition of the energy dependent Na/K ATPase pumps. 48 These findings argue against the pump-leak hypothesis of cell volume regulation, 49 which is based on the impermeability of the membranes to extracellular sodium as a compensatory mechanism for the osmotic pressure of intracellular proteins.…”
Section: àmentioning
confidence: 99%